Welsh Language Fanfiction in Light of Welsh Cultural and National Identity and Language Revitalisation - Zduńczyk, Nikola; Rogulska, Marta; Sokulski, Daniel (Studia Celtica Posnaniensia, 2023)
While the field of fan studies is constantly growing, it has been scarcely researched in relation to minority languages and language revitalisation. In this paper we have undertaken to explore the small and previously unexplored realm of Welsh-language fanfiction, focusing on the motivations to read and write it. The aim was to explore the possible role of fanfiction in language revitalisation by investigating a relationship between these motivations and the cultural and national identity of the authors and readers, as well as their attitude towards the Welsh language. The article presents the results of a study conducted in 2022 through the use of online surveys on a sample of readers of Welsh-language fanfiction found on the Tumblr platform, and semi-structured interviews with authors of fanfiction posted on Archive of Our Own. The study revealed that the decision to participate in the fandom was strongly connected to the cultural, and in particular linguistic identity of authors and readers, and to a much lesser extent to their national identity. Two out of three major motivations emerging from the study: a wish to broaden the use of language online and the wish to learn it can be connected with language revitalization. Engagement with fanfiction was perceived as an accessible form of leisure available in Welsh and as a safe space for both learners and native speakers to creatively use the language without fear of criticism, which suggests the importance and possible use of fandom in language revitalisation. However, the study also points to some difficulties in developing a fan community around Welsh fanfiction, mostly due to technical limitations and the small amount of popular media created originally in Welsh.